Life Accounts and Pedagogic Knowledge from Urban and Rural Teachers - Daniel Bezerra de Brito (Universidade Federal do Rio Grande do Sul, 2015)
This article discusses the profile and life accounts of 40 local teachers working with preschool education in urban and rural areas within Rio Grande do Norte state. Stories revealed that their personal and professional careers, from experience-based knowledge, affect their pedagogic practices. Links between personal and professional life were assessed in this article from a sociologic perspective, as individual and social histories between educators and the groups or social field to which they belong. The subjectivity of such relations, comprised in the stories, was understood as intentional information, though hiding rhetoric discourses aimed by the educators at their groups - family, school and profession, among others.